The Evaluation of Prevention and Handling Program Policy for Human Trafficking - Sarihati, Tati; Mukhlisiana , Lusy; Krisnayana, Riefky (International Journal of Psychosocial Rehabilitation, 2020)
West Java is the sending area of victims and top ranking with ± 30% of all human trafficking cases in Indonesia. The handling of these cases has not been effective, even though there is a special program for this. Bardach’s evaluation theory in Patton & Sawicki (Patton, 1986) is used to analyse this research problem based on policy evaluation dimensions, which are technical feasibility, economic and financial possibilities, political feasibility, and administrative operations. For the effectiveness variable, Yuchman and Seashore’s theory in Steers (Steers, 1996) is used based on the target, function, and system source dimensions. The purpose of this study is to analyse the policy evaluation factors that influence the effectiveness of the program. The explanatory survey method was used with the source of data collection on library studies and field studies, which included questionnaires, observations, and interviews, using saturated samples as the sampling techniques and simple linear regression as the data analysis technique. The results showed a positive and significant effect between policy evaluations on the effectiveness of the Prevention and Handling Program on Human Trafficking in the General Criminal Directorate of West Java Regional Police. In addition, other variables related to the program were also found.